2016
DOI: 10.1038/ni.3434
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis induces the miR-33 locus to reprogram autophagy and host lipid metabolism

Abstract: Mycobacterium tuberculosis (Mtb) survives within macrophages by evading delivery to the lysosome and promoting the accumulation of lipid bodies, which serve as a bacterial source of nutrients. Here we show that by inducing miR-33 and its passenger strand miR-33*, Mtb inhibits integrated pathways involved in autophagy, lysosomal function and fatty acid oxidation to support bacterial replication. Silencing of miR-33 and miR-33* by genetic or pharmacological means promotes autophagy flux through derepression of k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
246
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(275 citation statements)
references
References 57 publications
10
246
2
1
Order By: Relevance
“…In addition, lipid-laden mycobacteria exhibit a drugresistance and dormancy-like phenotype, characteristics associated with latent infection (57). A recent study reported that M. tuberculosis-induced miR-33/33* inhibited FAO and enhanced lipid-body formation in macrophages (23). Importantly, we found that PPAR-a activation promoted lipid catabolism and upregulated the expression of genes involved in FAO in M. tuberculosisinfected macrophages.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…In addition, lipid-laden mycobacteria exhibit a drugresistance and dormancy-like phenotype, characteristics associated with latent infection (57). A recent study reported that M. tuberculosis-induced miR-33/33* inhibited FAO and enhanced lipid-body formation in macrophages (23). Importantly, we found that PPAR-a activation promoted lipid catabolism and upregulated the expression of genes involved in FAO in M. tuberculosisinfected macrophages.…”
Section: Discussionmentioning
confidence: 46%
“…Previous studies also reported that TFEB plays a crucial role in the link between lipophagy and FAO and in the transcriptional regulation of genes involved in several steps of lipid degradation (16). Moreover, silencing of miR-33/33* decreased lipid accumulation and induced lipolysis, which were correlated with increased xenophagy and antimicrobial responses against M. tuberculosis in macrophages (23). Thus, these data suggest that PPAR-a activation induces lipid catabolism to enhance destruction of the foamy refuges of mycobacteria in host cells.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…miR-33 controls M2 polarization through the alteration of mitochondrial function 18 and key metabolic (AMP-activated protein kinase) 19 and autophagy effectors, 20,21 of high relevance to atherosclerosis and associated cardiometabolic diseases. Long-term inhibition of miR-33 (subcutaneous anti-miR) in C57/Bl6 mice fed a high-fat diet upregulates hepatic ABCA1 (but not SREBP1), promotes whole-body oxidative metabolism and M2 polarization in adipose tissue, and decreases circulating triglyceride levels, although it does not improve insulin resistance.…”
Section: Lipid Handlingmentioning
confidence: 99%
“…Another study reported that Mtb regulates miR-155 through an ESAT6-dependent manner to overcome its elimination and promote infection in macrophages (Kumar et al, 2012). Mtb also induces miR-33 and its passenger strand to inhibit integrated pathways involved in autophagy and reprogram host lipid metabolism to enable intracellular survival (Ouimet et al, 2016). Mtb blocks the autophagic machinery by blocking phagosome maturation through secretion of the macromolecules, PtpA and SapM.…”
Section: Mycobacteria Can Block Autophagosome Maturation To Create Amentioning
confidence: 99%